2019
DOI: 10.1016/j.epsl.2019.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Xenon and iodine behaviour in magmas

Abstract: Iodine (I) and xenon (Xe) are two key elements that trace Earth's differentiation (e.g. atmosphere formation) and dynamics (e.g. volcanism and recycling at subduction zones). Iodine and Xe abundances are linked through the decay of the extinct 129 I that produced 129 Xe, which is today depleted in the Earth's atmosphere compared to the composition of the solar system (i.e. chondrites). Iodine and Xe cycles and storage in the deep Earth are almost unknown, which is in large part due to the fact that their behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…Cicconi et al [14] dissolved ~4 mol.% I in B 2 O 3 -rich glass compositions held at pressure of 150 MPa; however, their investigated compositions (~60 wt.% B 2 O 3 ) were less relevant for the I immobilization in nuclear waste matrices. A comparable behaviour was also observed as a function of pressure for I in boron-free silicate glasses compositions with applications to Earth Sciences [16,17]. Leroy et al [17] showed that I solubility can reach up to 1.5 mol.% in Si-poor H 2 Orich silicate glasses synthesised at 3.5 GPa.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Cicconi et al [14] dissolved ~4 mol.% I in B 2 O 3 -rich glass compositions held at pressure of 150 MPa; however, their investigated compositions (~60 wt.% B 2 O 3 ) were less relevant for the I immobilization in nuclear waste matrices. A comparable behaviour was also observed as a function of pressure for I in boron-free silicate glasses compositions with applications to Earth Sciences [16,17]. Leroy et al [17] showed that I solubility can reach up to 1.5 mol.% in Si-poor H 2 Orich silicate glasses synthesised at 3.5 GPa.…”
Section: Introductionmentioning
confidence: 60%
“…A comparable behaviour was also observed as a function of pressure for I in boron-free silicate glasses compositions with applications to Earth Sciences [16,17]. Leroy et al [17] showed that I solubility can reach up to 1.5 mol.% in Si-poor H 2 Orich silicate glasses synthesised at 3.5 GPa.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…More recently, Morizet et al [33] showed that the iodine solubility could be further increased by using highly oxidizing conditions promoting the formation of iodate species (I 5+ ) within the glass structure. Regardless, the strong increase in the iodine solubility is ascribed to the increase in thermodynamic activity of the fluidic iodine in equilibrium with the melt phase upon pressure [30,34,35]. Although, this represents a major breakthrough in the race for immobilizing efficiently iodine radioisotopes, we still lack a clear fundamental understanding on how iodine behave as a function of glass composition.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in the incorporation of Iodine (I) in glasses in the past few years, especially in the field of Earth sciences 1,2 and in the nuclear waste glasses community. [3][4][5][6][7][8] I has an active radioisotope ( 129 I) that is produced from the nuclear fission of actinides.…”
Section: Introductionmentioning
confidence: 99%